Exploiting spectral differences between two acoustic imaging methods for the in situ evaluation of surface-breaking cracks in asphalt. (15th December 2019) - Iodice, M.; Muggleton, J.M.; Rustighi, E.
Abstract: The assessment of the location and the extension of cracks in roads is important for determining the potential level of deterioration in the road overall and in the infrastructure buried beneath it. Damage in a pavement structure is usually initiated in the tarmac layers, making Rayleigh waves ideally suited for the detection of shallow surface defects. In this work, the differences between the spectral images obtained with the Multichannel Analysis of Surface Waves (MASW) and the Multiple Impact of Surface Waves (MISW) are suggested for the first time to detect, locate and evaluate surface-breaking cracks in dispersive material, i.e. roads. Assessment of crack in roads is usually performed assuming constant velocity and non-dispersive behaviour of the material tested, limiting this approach to the very shallow layer of the road. The road is here holistically treated as a dispersive medium, supporting a paradigm-shifting approach to in situ crack evaluation. It is shown that surface-breaking cracks influence the content of the spectral images obtained with these two acoustic imaging techniques. Their differences are used for the first time for the in situ evaluation of the presence, the location and, in some cases, the extension of vertical cracks in roads. The study is conducted through numerical simulations, alongside experimental investigations. The paper describes two cases for which the cracking is internal and then external to the deployment of sensors. The method proposed in this paper proved to be successful for the in situ evaluation of cracks in asphalt, tackling the heterogeneities and dispersive behaviour of the material tested.